2019
DOI: 10.1111/evo.13868
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene glacial cycles drove lineage diversification and fusion in the Yosemite toad (Anaxyrus canorus)

Abstract: Species endemic to alpine environments can evolve via steep ecological selection gradients between lowland and upland environments. Additionally, many alpine environments have faced repeated glacial episodes over the past two million years, fracturing these endemics into isolated populations. In this “glacial pulse” model of alpine diversification, cycles of allopatry and ecologically divergent glacial refugia play a role in generating biodiversity, including novel admixed (“fused”) lineages. We tested for pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 158 publications
(255 reference statements)
2
50
0
Order By: Relevance
“…Advancements in sequencing technology have given rise to an increased availability of high-throughput sequence data for use in phylogeographic studies (Garrick et al, 2015), which has in turn allowed researchers to compare more complex models of demographic history (e.g., Smith et al, 2017). Although it has long been suggested that the expansion and contraction of species ranges in response to glacial cycles led to the formation of many hybrid zones (Hewitt, 2011;Stebbins, 1985), the use of high-throughput sequence data in phylogeographic studies has increased awareness of the prevalence and complexity of gene flow and hybridization in species' responses to climatic change (Maier et al, 2019;Ruffley et al, 2018;Smith & Carstens, 2020). There are numerous potential outcomes of secondary contact, but some well-known examples include lineage fusion (Petit et al, 2003), adaptive introgression (Anderson & Stebbins, 1954), and speciation via reinforcement (Butlin, 1987).…”
mentioning
confidence: 99%
“…Advancements in sequencing technology have given rise to an increased availability of high-throughput sequence data for use in phylogeographic studies (Garrick et al, 2015), which has in turn allowed researchers to compare more complex models of demographic history (e.g., Smith et al, 2017). Although it has long been suggested that the expansion and contraction of species ranges in response to glacial cycles led to the formation of many hybrid zones (Hewitt, 2011;Stebbins, 1985), the use of high-throughput sequence data in phylogeographic studies has increased awareness of the prevalence and complexity of gene flow and hybridization in species' responses to climatic change (Maier et al, 2019;Ruffley et al, 2018;Smith & Carstens, 2020). There are numerous potential outcomes of secondary contact, but some well-known examples include lineage fusion (Petit et al, 2003), adaptive introgression (Anderson & Stebbins, 1954), and speciation via reinforcement (Butlin, 1987).…”
mentioning
confidence: 99%
“…To do so, all RADseq tags were exported from the Stacks catalogue using populations.pl and the --fasta-samples flag ( Catchen et al, 2013 ). The fasta file was converted to phylip format using the python script fasta2genotype.py ( Maier et al, 2019 ), and by doing so, also loci with excess heterozygosity (>65%) were removed to filter for paralogs. For further analysis, the individuals with the lowest amount of missing data were selected from each of the three clusters, resulting in an alignment with 29 individuals (Western Group 10, South-Eastern Subgroup 9, and North-Eastern Subgroup 10).…”
Section: Methodsmentioning
confidence: 99%
“…Isolation periods contributed to genetic and phenotypic differentiation, fueling allopatric adaptive (i.e., divergent natural selection) and nonadaptive (i.e., genetic-drift) lineage divergence and/or reinforcing existing species boundaries (Hewitt 1996(Hewitt , 1999Czekanski-Moir and Rundell 2019). If reproductive isolation did not evolve while in refugia, secondary contact during range shifts resulted in the collapse of formerly distinct lineages (i.e., speciation reversal; Kearns et al 2018;Maier et al 2019), introgressive hybridization (e.g., Salzburger et al 2002;Schweizer et al 2019), or even contributed to complete the speciation process via reinforcement of reproductive isolation (Butlin and Hewitt 1985;Hewitt 1996;Nevado et al 2018). For these reasons, Pleistocene glacial cycles have been considered to both promote range fragmentation and allopatric speciation (Knowles 2000) and inhibit speciation through genetic homogenization (Zink and Slowinski 1995;Klicka and Zink 1997).…”
Section: Introductionmentioning
confidence: 99%